The 2024 constitutional reform of the judiciary: challenges in evaluation, committee integration, and electoral campaigns - del Rosario Rodríguez, Marcos (Revista Internacional & Comparada de Derechos Humanos, 2026)
The constitutional reform to the Mexican Judiciary published on September 15, 2024, introduced an unprecedented system of popular elections for judges and justices. This article examines the main implementation challenges of this reform, focusing on three issues: (1) the lack of uniform methodologies for evaluating and selecting judicial candidates; (2) the deficient composition of evaluation committees, which lack neutrality, proven track record, and professional recognition; and (3) the risks arising from judicial election campaigns, including political propaganda, campaign financing, and the erosion of impartiality. The article concludes that although improvements to the judicial appointment system are necessary, it is crucial to implement rigorous evaluation methods and standardized criteria for committee composition as measures to mitigate the risks of the electoral selection model and to ensure that merit and independence remain paramount in the judiciary